2005
DOI: 10.1002/lt.20663
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation—Adult donor outcomes: A systematic review

Abstract: The objective of this study was to evaluate the safety and efficacy of adult-to-adult living donor liver transplantation, specifically donor outcomes. A systematic review, with searches of the literature up to January 2004, was undertaken. Two hundred and fourteen studies provided information on donor outcomes. The majority of these were case series studies, although there were also studies comparing living donor liver transplantation with deceased donor liver transplantation. Both underreporting and duplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
3
9

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(209 citation statements)
references
References 38 publications
8
189
3
9
Order By: Relevance
“…These hypothetical studies, however, neglected the risk to the living donor in the analysis. A systematic review of published data showed that the reported morbidity after donor hepatectomy varied widely from 0%-100%, with a median of 16% [47]. In Asia, donor morbidity was 15% from an international survey [48] and 12% from a multicenter study in Japan [49].…”
Section: Ldltmentioning
confidence: 99%
“…These hypothetical studies, however, neglected the risk to the living donor in the analysis. A systematic review of published data showed that the reported morbidity after donor hepatectomy varied widely from 0%-100%, with a median of 16% [47]. In Asia, donor morbidity was 15% from an international survey [48] and 12% from a multicenter study in Japan [49].…”
Section: Ldltmentioning
confidence: 99%
“…The mortality of liver donation has been reported to be about 0.2% (probably an underestimate since there is no registry in many countries which perform LDLT) and the morbidity has been estimated to be 0-100% depending on how it is measured. 21 It is also clear that as center experience grows, the incidence of serious complications decreases. 22 The risk to the donor would not be justifiable if there is little possibility of the recipient surviving long-term as when there is extrahepatic disease or gross vascular invasion.…”
Section: The Role Of Living Donor Liver Transplantationmentioning
confidence: 99%
“…The calculated risk of mortality from kidney donation is approximately 2 in 10 000 24 and is up to 10-fold greater for a left lateral segment living liver donation (with the right-lobe having a greater risk than left-lobe). 25 There are also risks of significant morbidity, including postoperative bleeding and infections. All donors experience acute pain, and some develop chronic pain.…”
Section: Risk/benefit Ratiomentioning
confidence: 99%
“…27 Other reviews have described the risk of morbidity as ranging from 0% to 100%. 25,28 The true rate of morbidity and mortality for other solid-organ donations is difficult to establish (eg, lung, pancreas, and small bowel) because of the small numbers of reported cases in the literature and the lack of living-donor registries. 29 Long-term risks for the potential child donor need to be considered as well, especially because there have been no long-term data on the safety of pediatric donation.…”
Section: Risk/benefit Ratiomentioning
confidence: 99%